2014
DOI: 10.1063/1.4897519
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of a vortex ring impacting a permeable wall

Abstract: In this paper, we numerically simulate a vortex ring impacting a permeable wall by using a lattice Boltzmann method. The study is motivated by recent publications on vortex ring/permeable wall interaction and our desire to address some of the unanswered questions such as evolution of core vorticity, kinetic energy, and enstrophy of the flow field during the interaction. The simulation was conducted for a wide range of parameters, namely, wall open-area ratios (ϕ) (0 ≤ ϕ ≤ 1), wire structure dimensions (A) (0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…It has been observed that the presence of a permeable wall leads to significant changes in the flow field, and the final outcome of the interaction is itself strongly influenced by surface permeability. Indeed, under certain favourable conditions, the primary vortex ring was observed to pass through the permeable wall and continue as a modified vortex ring in its lee [20]. A vortex ring can also interact with another one, as can be observed in the head-on collision of two vortex rings.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been observed that the presence of a permeable wall leads to significant changes in the flow field, and the final outcome of the interaction is itself strongly influenced by surface permeability. Indeed, under certain favourable conditions, the primary vortex ring was observed to pass through the permeable wall and continue as a modified vortex ring in its lee [20]. A vortex ring can also interact with another one, as can be observed in the head-on collision of two vortex rings.…”
Section: Introductionmentioning
confidence: 96%
“…The second, and richer, category of vortex ring instability consists of coupled instabilities associated with the primary vortex ring undergoing an interaction, for example with another ring [17] or with a boundary such as a wall [18][19][20]. Such coupled instabilities are typically more complicated than the more studied isolated instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…23 The code has been extensively validated for several benchmark problems involving the motion of a vortex ring in viscous liquid. [18][19][20] Interested readers are referred to Refs. 18-20 for the implementation details.…”
mentioning
confidence: 99%
“…As far as we are aware, this has not been carried out previously. To study the motion of multiple coaxial viscous vortex rings, the lattice Boltzmann method (LBM), which has been previously verified and applied to vortex dynamics, [18][19][20] is used to simulate the motion of multiple viscous rings.…”
mentioning
confidence: 99%
“…Yamada et al (1982) and Walker et al (1987) experimentally observed fingering of vortex ring after the impingement. Interaction with other type of solid objects was reported by Naaktgeboren et al (2012), Cheng et al (2014), andMujal-Colilles et al (2015) for permeable plates. Suzuki and Kumagai et al (2007), Masuda et al (2012), Bethke et al (2012), and Misaka (2012) studied particulate layers transported by a vortex ring.…”
Section: Introductionmentioning
confidence: 88%